The Effect of Using PQ4R (Preview, Question, Read, Reflect, Recite, Review) Strategy on EFL Students’ Reading Comprehension Achievement - Dwi Eka Martina (Universitas Syiah Kuala, 2018)
The research aims to find out whether PQ4R (Preview, Question, Read, Reflect, Recite, Review) strategy that developed by Thomas E.L and Robinson H. A (1972) improved students’ reading comprehension. The population was all of the students of SMP Negeri 1 Karang Baru, Aceh Tamiang. The sample was the students of class IX-A which consisted of 32 students. The researcher used simple random sampling to choose the sample. She conducted pre-test, treatment, and post-test to collect data. It was found that mean score of pre-test was under the KKM, while the mean score of post-test was pass the KKM. The gain score was 21.09. It indicated there was an improvement of students’ achievement. Moreover, the analysis of t-test showed that tscorettable or 9.66 2.042 at the level of significance 0.05 with the degree of freedom (df) 30. It is clear that the alternative hypothesis (Ha) is accepted. It means that PQ4R is an effective strategy in teaching reading.